Splenic Vein Aneurysm Mimicking Endocrine Pancreatic Tumor - Dalla Bona, Enrico; Beltrame, Valentina; Liessi, Guido; Liessi, Federica; Pasquali, Claudio; Sperti, Cosimo (JOP. Journal of the Pancreas, 2013)
Context Splenic vein aneurysm (SVA) is an extremely rare vascular abnormality, and is usually caused by portal hypertension. Symptoms are unusual, but may include rupture or abdominal pain. Diagnosis is usually made by duplex ultrasonography or computed assisted tomography: detection by magnetic resonance is infrequent. Due to a rarity of this pathology, treatment is unclear, and varies from non-invasive follow-up to surgical excision. Case report A 60-year-old man with a 14-year history of ulcerative colitis, presented with a 3-month history of ischemic artery disease of the right leg. CT angiography showed stenosis of the right, external femoral artery, and a 1 cm solid, hypervascular lesion in the body of the pancreas. Magnetic resonance imaging (MRI) confirmed a 17 mm nodule in the pancreatic body, near to splenic vein. A suspicion of endocrine tumor of the pancreas was made, and the patient was referred to our department 5 months later. A PET/TC with Ga68 (DOTATOC) failed to show any pathologic uptake of the radiotracer. Serum hormonal assays were in the normal range. The patient underwent abdominal MRI that showed a 1 cm lesion of the body of the pancreas with the same signal intensity of the splenic vein. Abdominal CT angiography revealed a 20x17 mm splenic vein ectasia. No neoplasms were detected into the pancreatic parenchyma either by CT or MRI; no abnormal findings in the portal or superior mesenteric veins were found. A follow-up with color Doppler ultrasonography or MRI was scheduled and after six months the patient is well: there was no change in the size or number of SVA. Conclusion Because the incidence of SVA is very low, the exact indication for intervention and the type of treatment is not well defined. Although follow-up is limited, as in our case, in asymptomatic patients with small aneurysms, observation and careful follow-up appear to be sufficient treatment. So, at this moment, each case must be individually evaluated.